ANALISIS RETURN ON ASSET (ROA), ECONOMIC VALUE ADDEAD (EVA) DAN MARKET VALUE ADDEAD (MVA) TERHADAP KINERJA KEUANGAN PERUSAHAAN PT. PERKEBUNAN NUSANTARA III (Persero) - Budi Gunawan; Teguh Erawati (Jurnal Akuntansi, 2015)
The purpose of this study was to determine the financial performance. Plantation Nusantara III (Persero) in the period 2009 to 2012 based on ReturnOn Assets (ROA), Economic Value Addead (EVA) and Market Value Addead (MVA) this study used purposive sampling. sample in this study is PT. Plantation Nusantara III (Persero) and objects in this study are already consolidated financial statements from 2009 to 2012 based on the results of this study indicate financial performance Return on assets is positive, Economic Value Addead is positive despite a four-period only happened one time period that negative values that occurred in the period of 2012 and Market Value Addead is positive. Keywords: financial performance, Retrun On Assets (ROA), Economic Value Addead (EVA) and Market Value Addaed (MVA).